PEMBUATAN MEJA GERGAJI POTONG KAYU UNTUK MENDUKUNG PRODUKSI KERAJINAN KAYU SAEKAY (JPMPPI (Jurnal Pengabdian Masyarakat), 2022)
The following Community Partnership Program involves an Implementing Team from the Department of Machinery, Banjarmasin State Polytechnic with partners from the Wood Craftsmen Business Unit. Partners are one of the work units of Individually Owned Enterprises (BUMP) with the business name SAEKAYU owned by Mr. Junaidi. Some of the problems currently facing Partners are limited equipment in the production of wood crafts, while the demand is quite high and the number of customers is decreasing due to non-fulfillment of demand. These various problems made the PKM Team follow up on partner problems by establishing cooperation to solve partner problems through the Community Partnership Program (PKM) by making equipment such as cutting tables that were donated to partners. The results of the following PKM activities can produce several things, including: (1) Increase the production of wood crafts; (2) Fulfillment of market demand; (3) increasing the knowledge and expertise of the Implementing Team and Partners in the field of science and technology; (4) improving the community's economy during the Covid-19 pandemic or post-pandemic. Keywords: Cutting Table, SAEKAYU